Pathways and Mechanisms for Cultivating Positive Psychological Qualities in College Students - Xu, Qun; Zhang, Mengmeng; Shi, Jingjing (Education Insights, 2026)
Positive psychological qualities play a vital role in stimulating individual potential, enhancing subjective well-being, and supporting the harmonious development of physical and mental health. Fostering positive psychological qualities among college students is of great significance for their comprehensive development and for the sustained progress of society. Through systematic cultivation, students are better able to develop in a confident and proactive manner, continuously enhance their adaptability, and effectively realize their personal value. At the same time, strengthening the development of positive psychology among college students embodies the educational philosophy of people-oriented development in higher education and contributes to their healthy and well-rounded growth. The cultivation of positive psychological qualities among college students is a sustained and coordinated process that benefits from the active participation of students, the professional guidance of educational institutions and teachers, the supportive involvement of families, and the collective support of society, forming a positive and synergistic educational environment.